First observation of the decay Bs0→Ds-Ds+ and measurement of its branching ratio - Aaltonen, T; Adelman, J; Akimoto, T; Albrow, MG; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Aoki, M; Apollinari, G; et al. (2008)
We report the observation of the exclusive decay Bs0→Ds-Ds+ at the 7.5 standard deviation level using 355pb-1 of data collected by the CDF II detector in pp̄ collisions at s=1.96TeV at the Fermilab Tevatron. We measure the relative branching ratio B(Bs0→Ds-Ds+)/B(B0→D-Ds+)=1.44-0.44+0.48. Using the world average value for B(B0→D-Ds+), we find B(Bs0→Ds-Ds+)= (9.4-4.2+4.4)×10-3. This provides a lower bound ΔΓsCP/Γs 2B(Bs0→Ds-Ds+)>1.2×10-2 at 95% C.L. © 2008 The American Physical Society.